Penerapan Model Experiential Learning untuk Meningkatkan Pemahaman Materi Cahaya dan Sifat-Sifatnya Siswa Kelas 5 SD - Citra Apriovilita Hariri; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The research purposes are to: (1) find out the application of Experiental Learning Model to improve the science understanding for Light and Its Properties subject material of fifth grade students in Temuguruh 1 Elementary School, and (2) increase the understanding of learning science through experiential learning model of fifth students I Temuguruh-Banyuwangi Elementary School. This study uses qualitative and quantitative research that applies classroom action. The research subjects are 19 fifth grade students which consists of 10 female and 9 male students. This research was conducted on March 13-25, 2017 in two cycles and each cycle contained two meetings. The data was collected by observation, interview, field notes, documentation, and test. The data analysis technique was done both in qualitative and quantitative analysis. The result of this research shows (1) the application of Experiential Learning Model in 4 phases, which are: the concrete experience, reflective observation, abstract conseptualisation, and active experimental that makes students to be more confident in delivering their opinion based on the observation that they have conducted; (2) science learning comprehension of student is improving through the application of Experiental Learning Model, it is proven by the increase average score in class from 72,2 became 73,4 in the first cycle and 79,6 in the second cycle. From 19 students in fifth grade, only 9 students passed the minimum standart of competency achievement of 47,4% (deficient). It changed from 11 students or 57,8% (satisfactory) in first cycle to 15 students or 78,9% (good) in second cycle.